Systemic inflammation and oxidative stress post-lung resection: effect of pretreatment with N-acetylcysteine - Bastin,AJ; Davies,N; Lim,E; Quinlan,GJ; Griffiths,MJ (Respirology, 2016)
Background and objectiveN-acetylcysteine has been used to treat a variety of lung diseases, where is it thought to have an antioxidant effect. In a randomized placebo-controlled double-blind study, the effect of N-acetylcysteine on systemic inflammation and oxidative damage was examined in patients undergoing lung resection, a human model of acute lung injury.MethodsEligible adults were randomized to receive preoperative infusion of N-acetylcysteine (240 mg/kg over 12 h) or placebo. Plasma thiols, interleukin-6, 8-isoprostane, ischaemia-modified albumin, red blood cell glutathione and exhaled breath condensate pH were measured pre- and post-operatively as markers of local and systemic inflammation and oxidative stress.ResultsPatients undergoing lung resection and one-lung ventilation exhibited significant postoperative inflammation and oxidative damage. Postoperative plasma thiol concentration was significantly higher in the N-acetylcysteine-treated group. However, there was no significant difference in any of the measured biomarkers of inflammation or oxidative damage, or in clinical outcomes, between N-acetylcysteine and placebo groups.ConclusionPreoperative administration of N-acetylcysteine did not attenuate postoperative systemic or pulmonary inflammation or oxidative damage after lung resection.